En quête de leaders locaux à Jakarta – regards croisés depuis Johannesburg - Claire Bénit-Gbaffou; Jérôme Tadié (L'Espace Politique)
This paper stems from deep debates engaged by to geographers working on politics in the city, and attempting to define the concept of « political informality ». They dispute in particular the place of the State in this definition – public norms, rules and practices in the shaping of power dynamics in the city. The conceptual debate is based on joint empirical fieldwork: based on Claire’s research in Johannesburg on local leadership, Jerome revisits with her his research sites in Jakarta – in quest of figures of local leaders in the city. The nature of these figures in Jakarta (and their differences with Johannesburg’s) reveals locally embedded political practices, and illuminates the specificities of each institutional, urban and socio-political contexts. The paper, constructed as a dialogue, illustrates the process of constructing academic thought – where concepts are eminently related to the local sites they aim at deciphering, and are constructed in iterative and dialogical ways. Its conclusion proposes an operational definition of the concept of “political informality” but also opens, for each author, to a different way of reading their own research sites, shaped by the encounter with the other.